1995
DOI: 10.1017/s0022215100130889
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EGF, EGFR and PCNA in laryngeal lesions

Abstract: The expression of EGF/EGFR in 47 laryngeal surgical specimens from 44 patients was examined. PCNA analysis as an index of proliferating cells was also performed in 32 cases of laryngeal cancer, six cases of pre-cancerous lesions and nine cases of normal laryngeal mucosa. EGFR failed to show a significant correlation with tumour behaviour, but EGF expression was statistically significantly higher in malignant (SCC) than in non-malignant tissues (pre-cancerous and normal tissues) (p<0.006), and PCNA also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
3
1
0
Order By: Relevance
“…The range of positive EGFR staining in head and neck squamous cell carcinoma has been reported from 55% to 100% 18–22 . In the present study, a high positive rate of EGFR staining was found in head and neck squamous cell carcinoma cases from the Asia–Pacific region, with 57% of strong staining or over‐expression of EGFR, which is similar to other studies reported as over‐expression in 42–80% of the cases 19,23 . A stronger EGFR staining was also observed with high extent of EGFR expression in head and neck squamous cell carcinoma in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The range of positive EGFR staining in head and neck squamous cell carcinoma has been reported from 55% to 100% 18–22 . In the present study, a high positive rate of EGFR staining was found in head and neck squamous cell carcinoma cases from the Asia–Pacific region, with 57% of strong staining or over‐expression of EGFR, which is similar to other studies reported as over‐expression in 42–80% of the cases 19,23 . A stronger EGFR staining was also observed with high extent of EGFR expression in head and neck squamous cell carcinoma in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The PCNA expression was significantly less for benign lesions than for malignant epithelium, in accordance with the findings of Shin et al (1993) and Wen et al (1995). This suggests that PCNA expression may be of value for differentiating benign from malignant squamous epithelial lesions.…”
Section: Discussionsupporting
confidence: 85%
“…Regards with this study, a high expression of EGFR staining was found in 101(67.3%) head and neck tumours (Table 3). This is in accordance with a study, which reported high expression of EGFR in 42-80% of the cases [5]. From this present study, high expression of EGFR was seen among both malignant and benign tumour of patients with head and neck (Table 3).…”
Section: Discussionsupporting
confidence: 93%